Financial education from a scientometric and a systematic literature review approach: Recent approaches and trends - Aranibar-Ramos, Edgar Romario (2023)
Financial education is a fundamental component of a sustainable and healthy financial life for individuals; thus, the absence of financial knowledge leads to detrimental financial behavior and exclusion, thereby limiting opportunities and diminishing the quality of life. The aim of this research was to provide a comprehensive analysis of current trends, thematic gaps, and future areas of research in financial education. To achieve this, a scientometric analysis and systematic literature review were conducted on the latest production in two highly regarded databases over the last five years. The findings reveal that the current production in this area is not experiencing significant growth in both databases and is predominantly in English. Additionally, technology plays a crucial role in granting access to financial information and tools. In this regard, financial education must be instilled from an early age to promote healthy financial habits. The study further highlights the obstacles in implementing effective financial education strategies and it emphasizes the need for further research in areas such as social relations, different contexts and populations, primary education, and informal and non-formal education.